Ansiedade à matemática : evidências de validade de ferramentas de avaliação e intervenção - Mendes, Alessandra Campanini (2016)
Mathematics anxiety is characterized by a specific set of unpleasant physiological, cognitive and behavioral reactions to any mathematical stimuli or mathematics learning contingencies. This paper had as a general objective to look for evidence of validity of assessment and intervention tools related to mathematics anxiety and to this end, the research was divided into two studies. The study part is intended to search for evidence of validity of the Mathematics Anxiety Scale (MAS). It is divided into three steps aiming in order to investigate the main objectives such as verify evidence of the inner structure of the MAS; check out correlations between high and low scores on the MAS and school performance in subject matters like mathematics, portuguese, history and geography; expand the application of the MAS in the South, Midwest and Northeast in Brazil and observe possible differences in average scores of mathematics anxiety in each region, taking into account students’ gender, school year (grades) and term. The second study aimed to verify the effectiveness of an intervention program to math anxiety and it was done in a single step. On the first study, the results in step 1, by Exploratory and Confirmatory Data Analysis, indicated that the MAS tends to show a structure with two dimensions. In part 2, the results showed that there was significant and positive correlation between MAS total score and performance in mathematics, in eleven two-month terms analyzed; Portuguese, in six two-month terms; History; in twomonth terms; Geography, in six two-month terms. In the third part, the results showed significant difference in MAS average in relation to the gender variable in the Midwest, southern regions and in the general sample. Referring to the period variable, there was also a significant difference in the Midwest, Southeast and also, in the general sample. On the school year variable, the significant differences in MAS average occurred in the Midwest and in the general sample. In the Midwest, the significant differences in MAS scores occurred between the 1st year of high school (9th grade) and the 6th and 7th years of elementary school. Significant differences were also observed between the 3rd grade and the 8th grade; the 6th grade and 8th and 1st grades; the 7th grade and 1st and 8th grades; and the 8th grade and 3rd, 6th and 7th grades. In the general sample, the differences between the 1st grade of high school (9th grade) and the 6th and 7th grades of elementary school. In relation to the general objective of this paper which is about the search for evidence of validity of an assessment tool and the effectiveness of an intervention, both concerned with math anxiety, data supporting positive evidence for carrying on using MAS and to the intervention were found in this research. Although the last one was only an initial study and thus it is still not possible to indicate whether it is effective, but the results are promising.